Frailty and maximal exercise capacity in adult lung transplant candidates. (October 2017) - Layton, Aimee M.; Armstrong, Hilary F.; Baldwin, Matthew R.; Podolanczuk, Anna J.; Pieszchata, Nicole M.; Singer, Jonathan P.; Arcasoy, Selim M.; Meza, Kimberly S.; D'Ovidio, Frank; Lederer, David J.
Abstract: Background: Frail lung transplant candidates are more likely to be delisted or die without receiving a transplant. Further knowledge of what frailty represents in this population will assist in developing interventions to prevent frailty from developing. We set out to determine whether frail lung transplant candidates have reduced exercise capacity independent of disease severity and diagnosis. Methods: Sixty-eight adult lung transplant candidates underwent cardiopulmonary exercise testing (CPET) and a frailty assessment (Fried's Frailty Phenotype (FFP)). Primary outcomes were peak workload and peak aerobic capacity ( V ˙ O 2 ). We used linear regression to adjust for age, gender, diagnosis, and lung allocation score (LAS). Results: The mean ± SD age was 57 ± 11 years, 51% were women, 57% had interstitial lung disease, 32% had chronic obstructive pulmonary disease, 11% had cystic fibrosis, and the mean LAS was 40.2 (range 19.2–94.5). In adjusted models, peak workload decreased by 10 W (95% CI 4.7 to 14.6) and peak V ˙ O 2 decreased by 1.8 mL/kg/min (95% CI 0.6 to 2.9) per 1 unit increment in FFP score. After adjustment, exercise tolerance was 38 W lower (95% CI 18.4 to 58.1) and peak V ˙ O 2 was 8.5 mL/kg/min lower (95% CI 3.3 to 13.7) among frail participants compared to non-frail participants. Frailty accounted for 16% of the variance (R 2 ) of watts and 19% of the variance of V ˙ O 2 in adjusted models. Conclusion: Frailty contributes to reduced exercise capacity among lung transplant candidates independent of disease severity. Highlights: Frail lung transplant candidates have reduced exercise capacity out of proportion to the severity of their lung disease. Frail lung transplant candidates have an average VO2 peak of less than 10 mL/kg/min. In lung transplant candidates, reduced aerobic muscle strength demonstrated the strongest correlation with frailty.